Evaluation of primary stability in modified implants: Analysis by resonance frequency and insertion torque - Sciasci, Plínio [UNESP]; Casalle, Nicole [UNESP]; Vaz, Luís Geraldo [UNESP] (Wiley, 2018)
Background: Changes in the macrogeometry of dental implants are known to influence primary stability and the osseointegration process. Purpose: The purpose of the present in vitro study was to evaluate the mechanical behavior of geometric changes in the apex region of dental implants. Methods: Thirty-five cylindrical dental implants (Titamax Ti; Neodent) were machined at the apical third to reproduce the experimental groups: without apical cut (Wc), apical bi-split cut, apical tri-split cut, apical quadri-split cut (Qs). One (control group) (Titamax Ti Ex) (n = 7) without any modifications was added. The implants had the same final dimensions (4.1 x 11 mm2). All implants were inserted into artificial bone blocks and were evaluated by insertion torque and resonance frequency by ISQ values (Osstell). Two-tailed analysis of variance (One-way ANOVA) and Tukey's post-test (P <.05). Results: Control and Qs implants showed a significant increase of the insertion torque (P <.001). For the resonance frequency, Wc and (control) implants had the greatest ISQ values. However, there's no significant difference between (control) and Qs for the ISQ values (P <.001). Conclusion: Within the limitations of the present study, the proposed geometries at the apical third of dental implants greatly influenced its insertion torque and primary stability in vitro.
Keywords: dental implant; implant design; insertion torque; primary stability; resonance frequency analysis